Cisco secure virtual private networks (CSVPN) : CCSP self-study - Mason, Andrew G. (Certification self-study series., 2004)
Cisco authorized self-study book for CCSP 642-511 foundation learning Understand the underlying principles of VPNs Learn about and identify proper implementation of remote access and site-to-site VPNs Identify the features, functions, and benefits of the Cisco VPN 3000 Concentrator Series Configure and test a remote access VPN using preshared keys on the Cisco VPN 3000 Concentrator Work with the RIP and OSPF dynamic routing protocols Gain proficiency with the VPN Client Firewall Apply digital certificates on the Cisco VPN 3000 Concentrator Use the Cisco 3002 Hardware Client to configure and test a remote access VPN Implement advanced VPN client features such as load balancing, reverse route injection, and the appropriate use of backup servers Configure LAN-to-LAN VPNs on the Cisco 3000 Concentrator Offer granular user-level security with user and unit authentication Learn how to use VPN through NAT and resolve real-world implementation challenges Provide a sound level of support and administration skills for day-to-day management of a VPN 3000 Concentrator-based VPN by utilizing the tools resident in the Concentrator CCSP Self-Study: Cisco Secure Virtual Private Networks (CSVPN), Second Edition, is a complete reference for professionals who intend to work with virtual private networks (VPNs) using IPSec. It includes detailed coverage of the VPN 3000 Concentrator, a scalable remote access platform that offers encryption, high availability, and superior performance. In addition to acting as a valuable study aid for the CCSP CSVPN 642-511 exam, this book is an invaluable theory and configuration guide for the VPN 3000 series of products, with its thorough coverage of concentrators, hardware clients, and software clients. CCSP Self-Study: Cisco Secure Virtual Private Networks (CSVPN), Second Edition, is a Cisco authorized, self-paced learning tool that helps you gain mastery over all techniques and technologies related to Cisco Systems VPN products. Chapter overviews bring you quickly up to speed and prepare you to get to work on securing your network. Detailed configuration examples allow you to take advantage of Cisco VPN products in no time. Unique chapter-ending review questions reinforce key concepts and test your knowledge. Whether you are seeking a reference guide to plan, administer, and maintain a VPN based upon the Cisco VPN 3000 Concentrator or are looking for a study guide for the 642-511 exam, CCSP Self-Study: Cisco Secure Virtual P ...